Prevalence of Amyloidosis in Korea - Su Ra Seo; Shin Yi Jang; Ga Yeon Lee; Bareun Choi; Heeran Chun; Eun Jeong Cho; Sung-il Cho (Orphanet Journal of Rare Diseases, 2017)
Abstract Background The aim of this study was to assess in amyloidosis prevalence in Korea between 2006 and 2015. Methods Primary diagnoses related to amyloidosis, regardless of subtype, were collected from the Korean National Health Insurance Service from 2006 through 2015. Results Overall, the age-standardized prevalence of amyloidosis was 0.93 (95% confidence interval (CI) 0.81, 1.04) persons per 100,000 persons in 2006 and 1.91 (95% CI 1.78, 2.05) persons per 100,000 persons in 2015. This included an increase from 0.43 (95% CI 0.35, 0.51) to 1.04 (95% CI 0.94, 1.14) persons per 100,000 persons in men and from 0.49 (95% CI 0.40, 0.57) to 0.87 (95% CI 0.77, 0.96) persons per 100,000 persons in women. In particular, the age-standardized prevalence of amyloidosis showed a greater increase in patients aged 65 years or older and in patients aged 45–64 years than in patients aged 20–44 years, for both men and women. Conclusions The overall age-standardized prevalence of amyloidosis was approximately 2 persons per 100,000 persons in 2015. The overall age-standardized prevalence of amyloidosis increased between 2006 and 2015, especially in individuals aged 45–64 and older than 65 years.